Corrective and new research frontier of dual-phase -lag non-fourier heat conduction in functionally graded cylindrical materials with bi-directional property variations - P. Das; M.A. Islam; M.A. Hasib (International Journal of Thermofluids)
This study presents a novel and corrective analysis of Dual-Phase-Lag (DPL) non-fourier heat conduction in functionally graded cylindrical materials with bi-directional property variations. For general purposes, the 2-D DPL model was employed and solved in a polar coordinate system for an FGM cylinder whose material properties vary exponentially in the axial and radial directions. The proposed model's analytical and numerical solutions were obtained through the SOV method and implicit FDM with a non-uniform grid. Moreover, the effect of the inhomogeneity parameter in the Fourier, Cattaneo–Vernotte (C–V), and DPL models has been analyzed. The results indicate that the DPL model achieves temperature stability in less time when contrasted with the C–V model. In addition, the reduced inhomogeneity parameters result in quicker attainment of a steady temperature and the induction of higher temperatures. The thermal wave propagation in the DPL model is consistently greater than that in the C–V model. In addition, an increase in time lag for heat flux enhances thermal wave properties (amplitude, wavelength, propagation speed etc.); conversely, an increase in time lag for temperature gradient counteracts wave properties and augments heat release. Nevertheless, the present outcomes offer a straightforward multivariate analytical and numerical solution for a finite cylinder's non-Fourier heat conduction equation under diverse boundary conditions.